(3GdbHS aj TQM ehWC eGdc Hf CfSs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s; (3eGdc Hf CfS Hf eGdc GdCUHMj GdMejQj, CHh YHO Gddg,J (B179 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN Gdabjg CHh GdbGSe YHO GdQMef bGd gPG cJGH GdbHS ai TQM ehWC GHf CfS QMeg dGdg hghChd cJGH Cda ai TQGFY GdESdGe s
(3BNQgG (B:s
(3aef ZaGQ GdPfhH fSCd QaY GdJbQjH hGdahR YfOg HGdefRd GdQMH GdbQjH s
(3GdfSNI HgG MhGTs
(3HChdgG agQSJs
(3HBNQgG EMOi hYTQhf hQbI eJeeI HNW fSN MOjKs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdMOjK h GdeUWdMs